A Shift in Ghana’s Educational Policy: a Boon or a Bane for the Country - ayembilla, Daniel; Ayanwale, Musa Adekunle (International Journal of New Education, 2025)
This study investigates the effects of new policies in Ghana on mission schools, emphasizing the perceptions of educators, administrators, parents, students, and community members. Employing a qualitative case study design, the research included a purposive sample of 56 students from five mission schools. Thematic analysis was performed to identify key themes related to educational policy changes and their impact on quality education. Stakeholders highlighted several factors associated with these policies that have negatively influenced educational standards, particularly the introduction of the Free Senior High School (FSHS) initiative. The effective implementation of the FSHS policy has been challenged by issues such as inadequate infrastructure, overcrowded classrooms, limited curricula, and insufficient funding. As a result, this study recomends greater stakeholder engagement in the policy development process to more effectively meet the needs of mission schools.